Retrospective Study Using Computed Tomography to Compare Sufficient Chest Compression Depth for Cardiopulmonary Resuscitation in Obese Patients - Lee, Heekyung (J Am Heart Assoc, 2019)
BACKGROUND: This study aimed to investigate the relationship between body mass index (BMI) and sufficient chest compression depth (CCD) in obese patients by a mathematical model. METHODS AND RESULTS: This retrospective analysis was performed with chest computed tomography images conducted between 2006 and 2018. We classified the selected individuals into underweight (<18.5), normal weight (≥18.5, <25), overweight (≥25, <30), and obese (≥30) groups according to BMI (kg/m(2)). We defined heart compression fraction (HCF) as [Formula: see text] and estimated under‐HCF (the value of HCF <20%), and over‐HCF (the residual depth <2 cm after simulation with chest compression depth 5 and 6 cm). We compared these outcomes between BMI groups. Of 30 342 individuals, 8856 were selected and classified into 4 BMI groups from a database. We randomly selected 100 individuals in each group and analyzed a total of 400 individuals’ cases. Higher BMI groups had a significantly decreased HCF with both 5 and 6 cm depth (P<0.001). The proportion of under‐HCF with both depths increased according to BMI group, whereas the proportion of over‐HCF decreased except for the 5 cm depth (P<0.001). The adjusted odds ratio of under‐HCF, according to BMI group after adjustment of age and sex, was 7.325 (95% CI, 3.412–15.726; P<0.001), with 5 cm and 10.517 (95% CI, 2.353–47.001; P=0.002) with 6 cm depth, respectively. CONCLUSIONS: The recommended chest compression depth of 5 to 6 cm in the current international guideline is unlikely to provide sufficient ejection fraction during cardiopulmonary resuscitation in obese patients.